Estrategias de posicionamiento en redes sociales para la adquisición de paquetes turísticos en la agencia Travel With Us en la ciudad de Babahoyo - González Villanueva, María Leonor (2020)
The priority of this research project is to identify the necessary strategies for positioning in social networks. Due to the great importance of the Internet today, new strategies have been generated on how to make a company known through the platforms already known as "social networks", these platforms have become a means for the mass movement of information and getting a good positioning in these can guarantee progress for a travel agency. The tourist, as a frequent consumer of social networks, demands that tourism companies make use of new technologies to make themselves known through these networks because the information reaches them in an easier and more personal way so that the client feels more comfortable at the time of knowing about the company in question. The great impact that has generated the millions of interactions that occur every day through social networks such as Instagram, Facebook, Twitter, among others, has generated the development of an area of marketing known as digital marketing whose main objective is to generate the promotion of an agency by digital means. The digital marketing is becoming a new method to be able to make negotiations at a global level without belonging to a conventional work, where being subjected to rigid schedules is usually a burden for most people. Everyone knows that the internet has a wide range of tools that facilitate instant contact with anyone. Some social networks have already been facilitated as tools to generate negotiations, using systems to capture and follow customers anywhere in the world through any device capable of connecting to the Internet, either computers or mobile phones.